Systematic review of the role of social inclusion within sustainable urban developments. Issue 1 (2nd January 2022) - Mirzoev, Tolib; Tull, Kerina I.; Winn, Neil; Mir, Ghazala; King, Natalie V; Wright, Judy M; Gong, Yun Yun
ABSTRACT: Rapid urbanisation presents multiple opportunities, but also poses challenges for equitable distribution of gains from socio-economic developments. This systematic review explored the role of social inclusion within the urban sustainability agenda. Sustainable urban developments were conceptualised as comprising environmental, spatial, social and economic perspectives; and social inclusion as entailing access to core services (healthcare) and resources (food). A search of five databases and grey literature returned 1, 015 articles; 26 papers were included following screening using pre-determined criteria. Data was analysed thematically. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations were followed. Most included studies were from North America and few were from Africa and Asia. More empirical than conceptual studies were found, and more focused on food than healthcare. Social inclusion was generally included within the urban sustainability but was often an autonomous component, rather than mainstreamed, within urban sustainability. Social inclusion was mostly related to multiple elements of sustainability, with the greatest focus on combinations of environmental, social and economic opportunities for under privileged groups. However, less consideration was given to gender, ethnicity and other aspects of intersectionality. Multiple theories contributed to transferability of lessons. Key policy implications include prioritising the most vulnerable socially excluded populations, ensuring equal representation in urban planning, designing people-centred systems, building partnerships with communities, considering socio-cultural-political-economic contexts, and recognising both intended and unintended effects. More research is needed in low and middle-income countries (LMICs) on the role of social inclusion in achieving sustainable development, using cross-disciplinary approaches.